KAJIAN PERANCANGAN ARENA OLAHRAGA ELEKTRONIK - Thea Amelia; J.M. Joko Priyono Santoso (Jurusan Arsitektur dan Perencanaan, 2019)
Developing sports is characterized by the emergence of new sports, one of them is esports which also developing every year. The competition has been held at the 2018 Asian Games, however the venue has not been used specifically for esports. Therefore, the design of the esports arena is the answer and also the typical building that is present and marks the millennial generation of its time. Literature studies were conducted on millennial generation, behaviour of millennial, millennial era, building types and esports to find out more about the design of the esports arena. The methods used are data collection method, primary and secondary, quantitative and qualitative descriptive method, interaction method, comparative method, analytical and synthesis method, graphical method, experimental method conducted with theoritical studies, matrix studies, space studies, space characteristics studies, precedent studies, site studies and surveys, and mass compositions studies. The study resulted program area and capacity, site design, concepts, forms of mass composition, and schematic spatial principles (floor plan). Based on the methods and studies conducted, the conclusion is esports arena designed, in accordance with the theme